HR AS A STEWARD OF THE SOCIAL ENTERPRISE: INTEGRATING ESG METRICS INTO PERFORMANCE AND REWARD SYSTEMS - Ignasius Wahyudi Arianto; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing emphasis on Environmental, Social, and Governance (ESG) principles has transformed the role of organizations from purely profit-driven entities to socially responsible enterprises. This shift toward stakeholder capitalism requires internal alignment of organizational systems, particularly human resource (HR) practices, with sustainability objectives. However, traditional performance management and reward systems remain largely focused on financial outcomes, creating a disconnect between ESG goals and employee behavior. This study examines how HR can act as a steward of the social enterprise by integrating ESG metrics into performance and reward systems. Using a conceptual and narrative literature review approach, the research synthesizes insights from ESG, HR management, and organizational behavior literature. The findings indicate that embedding ESG into organizational culture, incorporating environmental and social KPIs into performance management, and aligning rewards with long-term sustainability goals are critical for effective implementation. The study also highlights the role of moderating factors such as leadership commitment, organizational culture, and regulatory context. A conceptual framework is proposed to explain how HR practices mediate the relationship between ESG strategy and organizational outcomes. The study concludes that integrating ESG into HR systems is essential for achieving sustainable performance and long-term value creation.